The customers' perception toward Secret Recipe's reputation by using the Reptrak™ model - Mohd Sah, Nur Farhana; Abdullah, Zulhamri (Springer, 2014)
Reputation is a key feature of a successful business. To be among the most precious intangible assets to a small business, the excellent reputation is taken into account. However, in order to assess the company reputation, the variety of dimensions of corporate reputation can be perceived in different ways by different customers. This study perceives that these differences are significant to find out customers’ perception toward the Secret Recipe’s reputation specifically by using seven key dimensions of the Reptrak™ model. Thus, a survey research was applied in this study. The survey was carried out in three different outlets of Secret Recipe. The questionnaire was comprised of 23 attributes which are divided in 7 key dimensions of the Reptrak™ model while four questions have been asked in order to measure good feeling, trust, esteem, and admiration that customers feel toward a company. This study concluded that by analyzing corporate reputation dimensions, the company would have a better understanding and decide on which reputation dimensions to focus besides ensuring that they still have a place in the customer’s heart as well as enhancing their reputation.